"What If I Don't Wanna Be White?": Black Authenticity and White Privilege in Margaret Seltzer's Fake Memoir. (3rd May 2016) - Bollinger, Heidi E.
ABSTRACT: This essay examines the discourse of black authenticity in Margaret Seltzer's fake memoir Love and Consequences (2008) and the author's fraudulent public performance as her narrator as a function of white privilege. Seltzer's hoax exploits stereotypes to appeal to a white middlebrow readership, demonstrating the continuing market value of black trauma.